KARAKTERISTIK FISIKOKIMIA, ORGANOLEPTIK DAN KANDUNGAN GIZI SELAI ALBEDO SEMANGKA YANG DITAMBAHKAN BUAH KERSEN - Septilina Melati Sirait; Imas Solihat; Hanafi Hanafi; Nurhasanah Nurhasanah; Alvina Nur Aini (AGROINTEK, 2023)
Watermelon albedo contains pectin, which is high enough to be processed into functional food ingredients. One of the foodstuffs that require pectin as a thickener is jam. In this study, watermelon albedo jam was added with Kersen fruit to increase the nutritional content in the form of antioxidants derived from Kersen. The purpose of this study was to analyze the physicochemical, organoleptic, and nutritional properties of watermelon albedo-Kersen fruit jam. Watermelon albedo-Kersen fruit jam has a sugar concentration of 65% and 0.1% citric acid. Observations of the shelf life were carried out every day for a week. Variations are made on adding preservatives namely, the addition of sodium benzoate and without sodium benzoate. The physicochemical parameters observed were pH value, soluble solids, greasing power, viscosity, syneresis, and organoleptic properties. While the nutritional content analysis included ash content, fat content, protein content, carbohydrate content, and water content. Watermelon albedo–Kersen fruit jam with the addition of sodium benzoate showed relatively better physicochemical properties and nutritional content than jam without the addition of sodium benzoate. The nutritional content of jam with the addition of sodium benzoate includes the ash content of 0.31%, the fat content of 0.41%, the protein content of 1.08%, the carbohydrate content of 11.20%, and the water content of 22.47%. Based on the panelists' preference test, the panelist's level of choice for the taste of jam was at a score of 4.8 (neutral–rather like), the panelist's level of choice for the color of the jam was at a score of 4.92 (neutral–rather liked). The panelist's level of choice for the texture of the jam is at a score of 5.2 (likes).